PERAN SISTEM PEMBAYARAN DIGITAL DALAM MENINGKATKAN PENJUALAN UMKM - Hutahaean, Limbert; Shabrina, Alifia Rahma; Martiani, Yasmin; Syakduzzaman, Syakduzzaman; Yulia, Astri; Gunardi, Gunardi (Jurnal Teknologi Komputer dan Informatika, 2024)
MSMEs (Micro, Small, and Medium Enterprises) have a crucial role in the economy, especially in developing countries like Indonesia. One of the main challenges faced by MSMEs is access to modern and efficient payment technology. This study aims to analyze the role of digital payment systems in increasing MSME sales. The research method used is a literature study by reviewing various relevant scientific literature. The results of the study show that the adoption of digital payment systems, such as electronic wallets (e-wallets), QRIS, and online bank transfers, can improve operational efficiency, reduce the risk of cash transactions, and expand the reach of the MSME market. The use of digital payment methods also allows MSMEs to increase financial transparency and more easily access financial services such as loans or investments. However, there are several challenges in implementing a digital payment system, including low digital literacy among MSME actors, limited technological infrastructure in several regions, and lack of socialization regarding the benefits of digitalization. Therefore, a comprehensive strategy is needed, such as increasing digital literacy and providing supporting infrastructure, to optimize the benefits of the digital payment system for MSMEs.